Acute Dilatation, Ischemia, and Necrosis of Stomach without Perforation. (7th October 2013) - Sahoo, Manash Ranjan; Kumar, Anil T.; Jaiswal, Sunil; Bhujabal, Siba Narayan
Abstract : Acute gastric dilatation can have multiple etiologies which may lead to ischemia of the stomach. Without proper timely diagnosis and treatment, potentially fatal events such as gastric perforation, haemorrhage, and other serious complications can occur. Here we present a 36-year-old man who came to the casualty with pain abdomen and distension for 2 days. Clinically, abdomen was asymmetrically distended more in the left hypochondrium and epigastrium region. Straight X-ray abdomen showed opacified left hypochondrium with nonspecific gaseous distension of bowel. Exploratory laparotomy revealed dilated stomach with patchy gangrene over lesser curvature and fundic area. About 4 litres of brownish fluid along with semisolid undigested food particles was sucked out (mainly undigested pieces of meat). Limited resection of gangrenous areas and primary repair were done along with feeding jejunostomy. Necrosis of the stomach was confirmed on histopathology. The patient recovered well and was discharged on the tenth postoperative day.